PENGARUH KONSEP PENDIDIKAN SYEKH AL-ZARNUJI TERHADAP KEAKTIFAN BELAJAR SANTRI - Dedi Supriatna (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
Almost in Islamic educational institution and pesantren in particular always teaches the study of Sheikh Al-Zarnuji's thought contained in his work namely Ta'lÃ®m Al-muta'allim TarÃ®q al-Ta'allum. Unfortunately, the underdevelopment of pesantren is always directed to the study of Sheikh Al-Zarnuji's thought. Because the book contains a very excessive doctrine about Ta'dzim so that the students were behave passively and static. As a result Pesantren is not able to face the challenges of today's world. This study aims to find out the concept of education Sheikh Al-Zarnuji, knowing the activities of students at boarding school Assalafiyyah 1 Babakan Tipar Cimahi Cicantayan Sukabumi and analyze the extent to which the education Concept Sheikh Al-Zarnuji affect the learning activities of students in boarding schools Assalafiyyah 1 Babakan Tipar Cimahi -Chicantayan Sukabumi. This research is descriptive-qualitative with field research type. By obtaining the data from Santri, Kiyai and the Board of Santri Putra through interview, observation also in the form of documents related to the research. Once the data is collected and recorded properly, the next step is to analyze the data. The process of analysis is done by reviewing all available data from various sources, then the data is analyzed and studied carefully and in the description which further gives description and explanation and described. The Effect of the Education Concept of Sheikh Al-Zarnuji in Ta'lim Al-muta'allim on the Activity of Student Learning at the Pondok Pesantren Assalafiyyah 1, there were 60% increase in attendance and 85% increase in the value of the students. So that the Activity of Studying Students of Pondok Pesantren Assalafiyyah 1 Babakan Tipar Cimahi-Cicantayan Sukabumi is influenced by the Education Concept of Sheikh Al-Zarnuji.